Boundary Discontinuous Fourier analysis of clamped isotropic and cross-ply laminated plates via Unified Formulation - (:unkn) unknown (Elsevier BV, 2024)
This paper presents an analytical solution for the static analysis of plates with clamped boundary conditions prescribed at the edges. The displacement field is expressed via the Carrera Unified Formulation (CUF) where an Equivalent-Single-Layer (ESL) ap...
Keywords: Análisis de Fourier; Placas laminadas